Matrix Metalloproteinases Are Differentially Regulated and Responsive to Compression Therapy in a Red Duroc Model of Hypertrophic Scar - Travis, Taryn E. (Eplasty, 2018)
Objective: Proteins of the matrix metalloproteinases family play a vital role in extracellular matrix maintenance and basic physiological processes in tissue homeostasis. The function and activities of matrix metalloproteinases in response to compression therapies have yet to be defined. Here, a swine model of hypertrophic scar was used to profile the transcription of all known 26 matrix metalloproteinases in scars treated with a precise compression dose. Methods: Full-thickness excisional wounds were created. Wounds underwent healing and scar formation. A subset of scars underwent 2 weeks of compression therapy. Biopsy specimens were preserved, and microarrays, reverse transcription-polymerase chain reaction, Western blotting, and immunohistochemistry were performed to characterize the transcription and expression of various matrix metalloproteinase family members. Results: Microarray results showed that 13 of the known 26 matrix metalloproteinases were differentially transcribed in wounds relative to the preinjury skin. The predominant upregulation of these matrix metalloproteinases during early wound-healing stages declined gradually in later stages of wound healing. The use of compression therapy reduced this decline in 10 of the 13 differentially regulated matrix metalloproteinases. Further investigation of MMP7 using reverse transcription-polymerase chain reaction confirmed the effect of compression on transcript levels. Assessment of MMP7 at the protein level using Western blotting and immunohistochemistry was concordant. Conclusions: In a swine model of hypertrophic scar, the application of compression to hypertrophic scar attenuated a trend of decreasing levels of matrix metalloproteinases during the process of hypertrophic wound healing, including MMP7, whose enzyme regulation was confirmed at the protein level.